A Dry‐Processed Al2O3/LiAlO2 Coating for Stabilizing the Cathode/Electrolyte Interface in High‐Ni NCM‐Based All‐Solid‐State Batteries (Adv. Mater. Interfaces 8/2022). Issue 8 (11th March 2022) - Negi, Rajendra S.; Yusim, Yuriy; Pan, Ruijun; Ahmed, Shamail; Volz, Kerstin; Takata, Ryo; Schmidt, Franz; Henss, Anja; Elm, Matthias T.
Abstract : Al2 O3 /LiAlO2 Coating for Thiophosphate‐Based All‐Solid‐State Batteries In article number 2101428, Rajendra S. Negi, Ruijun Pan, Anja Henss, Matthias T. Elm, and co‐workers demonstrate the beneficial effect of a high‐temperature treatment on several structural properties of dry‐processed Al2 O3 cathode coatings, such as reduced porosity and improved interfacial contact between cathode active material and solid electrolyte, which improves the electrochemical performance of thiophosphate‐based all‐solid‐state batteries. Cover design by Elisa Monte.